Mechanical Love - Ambo, Phie (Dyekjær, Sigrid, 2007)
Verzio FF The ability to love and be loved is one of the basic definitions of humans. Nevertheless, as modern technology increasingly encroaches upon people's everyday lives, this idea might need to be redefined, i.e. how does artificial intelligence fit into this concept? Director Phie Ambo follows the story of Professor Hiroshi Ishiguro from Osaka University who creates a Geminoid – a remote–controlled duplicate of himself – and prepares to introduce him to his wife and daughter. Another Japanese scientist creates an artificial baby seal called Paro, who keeps lonely and mentally handicapped people company and demonstrably increases their brain activity as a result. The animal–robot responds to the voice of its owners and can even "remember" its name with the aid of sensors. Naturally, these innovations necessarily give rise to some ethical questions: Is it right to allow someone to live under the illusion that they are "loved" by a machine, which does not have the same feelings for them? And then there is the old question about robotics itself: If machines can replace us, are we therefore not totally redundant?